Macular hole and vitreous hemorrhage subsequent to stereotactic hypofractionated radiotherapy for choroidal melanoma: A case report and review of the literature - Zhou, Xiaoyin; Ishikawa, Hiroto; Gomi, Fumi (Frontiers in Oncology, 2022)
Choroidal melanoma is the leading primary intraocular tumor with potentially fatal outcomes in adults. The coexistence of choroidal melanoma and a macular hole is extremely rare, and treatment strategies and information on the prognosis of associated complications are currently lacking. We report the first case of choroidal melanoma complicated with a macular hole and vitreous hemorrhage after stereotactic hypofractionated radiotherapy in Japan, and review the relevant literature in relation to the possible mechanisms, treatment strategies, and outcomes. An 83-year-old male with choroidal melanoma was treated with stereotactic hypofractionated radiotherapy in January 2021. Five months later, a full-thickness macular hole developed, followed by an acute massive vitreous hemorrhage about 2 weeks later. Following confirmation of tumor regression, the patient underwent a pars plana vitrectomy and internal limiting membrane peeling. The macular hole was closed postoperatively and the patient’s best-corrected visual acuity improved to 20/125. There was no evidence of intraocular tumor dissemination or distant metastases during follow-up. A systematic literature search only identified 10 previous cases of choroidal melanoma with a macular hole in eight reports worldwide, mainly in females. Macular edema may be the primary cause of macular hole formation in these cases. Most patients who underwent vitrectomy for complications after tumor regression achieved a good prognosis. The development of a macular hole is a rare complication associated with choroidal melanoma. Anterior-posterior traction of posterior vitreous detachment and secondary macular edema may have contributed to the formation of the macular hole in the current case.